2017
DOI: 10.3928/23258160-20161219-05
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Aflibercept for Neovascular Polypoidal Choroidal Vasculopathy in a Predominantly Non-Asian Population: RIVAL Results

Abstract: At 1 year, neovascular PCV in a predominantly non-Asian population treated with IAI demonstrated favorable visual, anatomic, and safety outcomes. [Ophthalmic Surg Lasers Imaging Retina. 2017;48:34-44.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The EVEREST II study found that combination therapy of full-dose PDT and intravitreal injections of ranibizumab was superior to monotherapy consisting of intravitreal injections of ranibizumab, in terms of BCVA and complete polyp regression [40]. However, recent studies suggest that anti-VEGF monotherapy with, for example, aflibercept has similar efficacy, at least in an Asian population [41,42].…”
Section: Specific Considerations When Treating Polypoidal Choroidal Vmentioning
confidence: 99%
“…The EVEREST II study found that combination therapy of full-dose PDT and intravitreal injections of ranibizumab was superior to monotherapy consisting of intravitreal injections of ranibizumab, in terms of BCVA and complete polyp regression [40]. However, recent studies suggest that anti-VEGF monotherapy with, for example, aflibercept has similar efficacy, at least in an Asian population [41,42].…”
Section: Specific Considerations When Treating Polypoidal Choroidal Vmentioning
confidence: 99%